2009
DOI: 10.1039/b808262f
|View full text |Cite
|
Sign up to set email alerts
|

Polyelectrolyte microcapsules for biomedical applications

Abstract: In this paper we review the recent contributions of polyelectrolyte microcapsules in the biomedical field, comprising in vitro and in vivo drug delivery as well as their applications as biosensors

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
247
0
4

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 281 publications
(254 citation statements)
references
References 127 publications
3
247
0
4
Order By: Relevance
“…In recent studies various active agents or model substances have been shown to integrate into hollow capsules (12)(13)(14)(15) or assemble into the multilayer without interference (14,16). Additional surface modification may further improve the properties of the carriers, for example enhancing their biocompatibility through functionalization with lipid layers (17) or improving their targeted uptake via antibody integration (18).…”
mentioning
confidence: 99%
“…In recent studies various active agents or model substances have been shown to integrate into hollow capsules (12)(13)(14)(15) or assemble into the multilayer without interference (14,16). Additional surface modification may further improve the properties of the carriers, for example enhancing their biocompatibility through functionalization with lipid layers (17) or improving their targeted uptake via antibody integration (18).…”
mentioning
confidence: 99%
“…However, several studies have pointed out that both planar films as well as capsules consisting of polyelectrolyte complexes do not exhibit significant toxicity. [7,100,101] Therefore, a thorough debate should be performed in order to assess in which conditions polycation related toxicity might be an issue or not. On the other hand, there are several research groups switching from the use of electrostatic interactions to the use of hydrogen bonding as driving for multilayer assembly, thus avoiding the use of polycations.…”
Section: Discussionmentioning
confidence: 99%
“…[6] While the polymeric shell is fully permeable to low molecular weight compounds such as ions and small drug molecules, they are impermeable to larger molecules. This property, schematically illustrated in Figure 1, renders polymeric multilayer capsules ideally suited for the encapsulation of biotherapeutics such as proteins, peptides, and nucleic acids like DNA, siRNA etc… [7][8][9] While the aqueous void of the capsules should provide physico-and bio-chemical stability to the molecules of interest, the capsule surface could be engineered in order to (1) target specific cell populations, (2) activate certain cell functions upon binding of the capsules to the cell surface or upon intracellular uptake, (3) release the capsule content at the required moment when reaching the target site or (4) upon a well-defined stimulus.…”
Section: Introductionmentioning
confidence: 99%
“…Polymeric NVs, in particular, are amenable to the incorporation of stimuli responsive components through blending with chemically responsive structural units [39]. Structures that can undergo morphogenic transformation via enzymatic degradation, pHinduced charge reversal, sol-gel transitions, redox sensitive bond cleavage, photo-induced cleavage or isomerization can be utilised to target biological environments that display the requisite parameters (or in the case of photosensitivity introduce an external stimulus) [40][41][42]. Such changes in the morphological properties of NVs would facilitate a concomitant activation or release of functional cargo in order to address the particular diseased tissue and, as such, have great clinical potential [43].…”
Section: Rd Generation (Work In Progress): Targeted Nanovectorsmentioning
confidence: 99%